Penerapan Model ASSURE dengan Media QuizAlize dalam Pembelajaran Mengidentifikasi Struktur dan Ciri Kebahasaan Teks Berita Kelas VII - Singgih Adi Nugroho; Laely Rohmawati; Titin Rahayu; Tegar Faik Wiji Wicaksono; Asep Purwo Yudi Utomo; Diyamon Prasandha (CV. Aksara Global, 2023)
The process of learning Indonesian still often uses conventional media, there is a lack of innovation in learning media that is in accordance with current technological advances so that students tend to get bored, and there is no use of QuizAlize media and the ASSURE model in Indonesian language learning class VII at SMP Negeri 9 Semarang become the background of this research. The purpose of this study was to obtain a description of the application of the ASSURE model with QuizAlize media in learning to identify the structure and language features of grade VII news texts. The benefits of this research are as a scientific contribution regarding the application of the ASSURE model with QuizAlize media, as well as providing knowledge about the application of the ASSURE model with QuizAlize media for readers. This type of research is Classroom Action Research with two cycles. 32 students of class VII G SMP Negeri 9 Semarang became the subject of this study. The data collection technique used is an observation technique. Then, qualitative descriptive analysis is the data analysis technique used. The results of the study in cycle I, the percentage of completeness was at 46.87%, while in cycle II it was 87.5%. The percentage increase is 40.63%. In addition, 17 students did not complete the first cycle, while in the second cycle there were 4 students. The increase in the accumulation of students who achieved mastery was 13 children. So, the accumulation of students who achieved completeness in cycle II was 28 children. Based on this, it can be concluded that the increase in the percentage of completeness in class VII G of SMP Negeri 9 Semarang is very good. Then, the application of the ASSURE model and QuizAlize media to this class can be said to be successful.